Developing Malaysia Madani: The Impact Of Gender And Student Origin (urban Vs. Rural) On Leadership, Citizenship, And Democratization In Malaysian Universities - Wan Khairul Aiman Wan Mokhtar; Mohd Nor Adzhar Ibrahim; Hasse Jubba; Saifuddin Zuhri Qudsy; Abdul Hanis Embong (Malaysian Institute of Planners (MIP), 2025)
Indexed Publication (Tier 2)